Composite flocculant for water treatment process and preparation method thereof
By preparing organic/inorganic composite flocculants and using multiple mechanisms to compound the flocculants significantly improve the adsorption ability of the flocculants to pollutants, solve the problems of low efficiency and fast saturation of montmorillonite adsorption of heavy metal ions, and realize an efficient water treatment process.
Patent Information
- Application Number
- CN202510054199.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-13
- Publication Date
- 2025-03-07
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing montmorillonite has limited efficiency in adsorbing heavy metal ions and is too fast to absorb saturation, making it difficult to meet the demand of water treatment processes for efficient pollutants removal.
By preparing organic/inorganic composite flocculants, the adsorption ability of flocculants to pollutants is significantly improved by using various mechanisms such as hydrophobic effect, electrostatic effect, and coordination effect on metal elements. The method includes mixing montmorillonite with hydrochloric acid solution and sonication, adding anhydrous ethanol and coupling agent for grinding and calcining, and then compounding with components such as chitosan and citral to finally form a composite flocculant with high adsorption capacity.
It improves the adsorption capacity and stability of flocculants to pollutants, significantly improves the COD removal rate of the water treatment process, and solves the problems of low efficiency and fast saturation speed of montmorillonite when adsorbing heavy metal ions.
Smart Images

Figure BDA0005240890180000101 
Figure BDA0005240890180000111
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of flocculants and relates to a composite flocculant for water treatment technology and a preparation method thereof. Background Art
[0002] With the advancement of industry, heavy metal pollutants generated by production activities continue to appear in water bodies. These pollutants not only pollute the environment, but may also accumulate through the food chain, posing a threat to human life and health. Therefore, researchers have explored a variety of technologies to deal with heavy metal pollution in water, such as electrochemical treatment, redox treatment and metallurgical treatment, which are highly efficient in dealing with heavy metals. However, they also face the limitations of high cost, high energy consumption and unsuitability for large-scale application.
[0003] Compared with other recycling technologies, the adsorption method has lower energy consumption in the reaction process and is simpler to operate. The adsorbent used in this method is not only environmentally friendly and low-cost, but also recyclable. Selecting a suitable adsorbent is the core of the adsorption method. Common adsorbent materials include resin, iron-based, aluminum-based and natural adsorbent materials.
[0004] Montmorillonite is widely used to remove heavy metal ions and organic pollutants from wastewater due to its easy access, environmental protection, huge reserves, excellent adsorption performance and low cost. Although there are many studies on the adsorption of heavy metals by montmorillonite, its natural morphology and structure limit its performance, resulting in some challenges in the adsorption of heavy metal ions, such as limited adsorption efficiency and too fast adsorption saturation rate. Summary of the invention
[0005] The purpose of the present invention is to provide a composite flocculant for water treatment process and a preparation method thereof. The present invention prepares an organic / inorganic composite flocculant, increases its stability, and utilizes a variety of mechanisms such as hydrophobic effect, electrostatic effect, and coordination effect on metal elements to significantly improve the flocculant's adsorption capacity for pollutants.
[0006] The purpose of the present invention can be achieved through the following technical solutions:
[0007] A method for preparing a composite flocculant for water treatment process comprises the following steps:
[0008] S1. Mixing montmorillonite and hydrochloric acid solution, ultrasonically treating the mixture, filtering out the mixture, vacuum drying the mixture to constant weight, adding anhydrous ethanol and a coupling agent, grinding and mixing the mixture, filtering, washing the mixture, drying the mixture to constant weight, calcining the mixture at high temperature, and cooling the mixture to room temperature to obtain modified montmorillonite;
[0009] S2. Under a nitrogen atmosphere, the modified montmorillonite and chitosan solution are mixed and ground, and the citral solution is added and stirred at a constant temperature, and then the solid is filtered out, washed, and vacuum dried to a constant weight to obtain a prefabricated flocculant;
[0010] S3. The prefabricated flocculant, modified cinnamyl alcohol, anhydrous ethanol and initiator are mixed and heated with stirring, solids are filtered out, washed and vacuum dried to constant weight to obtain the product.
[0011] As a preferred technical solution of the present invention, in step S1, the mass ratio of the montmorillonite, the hydrochloric acid solution, the anhydrous ethanol and the coupling agent is 8-10:40-45:30-35:2.2-2.5; the coupling agent is aluminate coupling agent DL-411.
[0012] As a preferred technical solution of the present invention, in step S1, the mass fraction of the hydrochloric acid solution is 15%; the ultrasonic treatment is performed at a power of 400-500W for 8-10 minutes; the grinding and mixing time is 50-60 minutes; the washing is performed three times with anhydrous ethanol; and the calcination is performed at a temperature of 300-320°C for 1.5-2.0 hours.
[0013] As a preferred technical solution of the present invention, in step S2, the mass ratio of the modified montmorillonite, chitosan solution and citral solution is 12-14:110-120:35-40; the chitosan solution is formed by mixing chitosan, acetic acid and deionized water in a mass ratio of 1.0-1.2:0.3-0.4:60-70; and the citral solution is formed by mixing citral and anhydrous ethanol in a mass ratio of 2.5-2.8:30-35.
[0014] As a preferred technical solution of the present invention, the molecular chain of chitosan is rich in amino, hydroxyl and N-acetylamino groups, which can construct cage-type molecules with a network structure through the action of hydrogen bonds and salt bonds, thereby capturing a variety of inorganic metal ions and organic compounds.
[0015] As a preferred technical solution of the present invention, chitosan and citral form a more stable Schiff base compound, further improving its ability to capture pollutants.
[0016] As a preferred technical solution of the present invention, in step S2, the grinding time is 30-40 minutes; the constant temperature stirring is stirring at 50-60°C and 500-600rpm for 5-6 hours; and the washing is washing three times with anhydrous ethanol.
[0017] As a preferred technical solution of the present invention, in step S3, the mass ratio of the prefabricated flocculant, modified cinnamyl alcohol, anhydrous ethanol and initiator is 20-23:3.2-3.6:70-80:0.10-0.12; the initiator is azobisisoheptonitrile.
[0018] As a preferred technical solution of the present invention, in step S3, the heating and stirring is stirring at a temperature of 68-72°C and a rotation speed of 400-500 rpm for 5-6 hours; and the washing is washing three times with anhydrous ethanol.
[0019] As a preferred technical solution of the present invention, the preparation method of the modified cinnamyl alcohol comprises the following steps: subjecting thioglycolic acid, cinnamyl alcohol, p-toluenesulfonic acid and toluene to a reflux reaction, and distilling under reduced pressure until no liquid is distilled out to obtain the modified cinnamyl alcohol.
[0020] As a preferred technical solution of the present invention, cinnamyl alcohol is grafted and modified to introduce a benzene ring structure with higher stability, thereby improving the hydrophobicity. At the same time, the introduced thiophenol group has a stronger metal ion adsorption capacity.
[0021] As a preferred technical solution of the present invention, the reflux reaction is a reflux reaction at 110-120°C for 4.0-4.5h; the usage ratio of the thioglycolic acid, cinnamyl alcohol, p-toluenesulfonic acid and toluene is 20-23g:52-60g:3.2-3.8g:160-170mL.
[0022] The invention discloses a composite flocculant for water treatment process prepared by the above preparation method.
[0023] Beneficial effects of the present invention:
[0024] The present invention prepares an organic / inorganic composite flocculant, increases its stability, and utilizes a variety of mechanisms such as hydrophobic effect, electrostatic effect, and coordination effect on metal elements to significantly improve the adsorption capacity of the flocculant on pollutants. DETAILED DESCRIPTION
[0025] In order to further illustrate the technical means and effects adopted by the present invention to achieve the predetermined invention purpose, the specific implementation methods, structures, features and effects of the present invention are described in detail below in combination with the embodiments.
[0026] Example 1
[0027] A method for preparing a composite flocculant for water treatment process comprises the following steps:
[0028] S1. Mix montmorillonite and hydrochloric acid solution, perform ultrasonic treatment, filter out, vacuum dry to constant weight, add anhydrous ethanol and coupling agent, grind and mix, filter, wash, dry to constant weight, calcine at high temperature, and cool to room temperature to obtain modified montmorillonite; wherein the mass ratio of montmorillonite, hydrochloric acid solution, anhydrous ethanol and coupling agent is 8:40:30:2.2; the coupling agent is aluminate coupling agent DL-411; the mass fraction of the hydrochloric acid solution is 15%; the ultrasonic treatment is 8 minutes at 400W power; the grinding and mixing time is 50 minutes; the washing is three times of washing with anhydrous ethanol; the calcination is calcined at 300°C for 1.5 hours; the vacuum drying temperature is 80°C; the drying temperature is 110°C;
[0029] S2. In a nitrogen atmosphere, the modified montmorillonite and chitosan solution are mixed and ground, and after adding citral solution and stirring at constant temperature, the solid is filtered, washed, and vacuum dried to constant weight to obtain a prefabricated flocculant; the mass ratio of the modified montmorillonite, chitosan solution and citral solution is 12:110:35; the chitosan solution is formed by mixing chitosan, acetic acid and deionized water in a mass ratio of 1.0:0.3:60; the citral solution is formed by mixing citral and anhydrous ethanol in a mass ratio of 2.5:30; the grinding time is 30 minutes; the constant temperature stirring is stirring at 50°C and 500rpm for 5 hours; the washing is washing three times with anhydrous ethanol; the vacuum drying temperature is 80°C;
[0030] S3. Mix the prefabricated flocculant, modified cinnamyl alcohol, anhydrous ethanol and initiator, heat and stir, filter out the solid, wash, and vacuum dry to constant weight to obtain; wherein the mass ratio of the prefabricated flocculant, modified cinnamyl alcohol, anhydrous ethanol and initiator is 20:3.2:70:0.10; the initiator is azobisisoheptanonitrile; the heating and stirring is stirring at a temperature of 68°C and a speed of 400rpm for 5h; the washing is washing three times with anhydrous ethanol; the vacuum drying temperature is 80°C.
[0031] The preparation method of the modified cinnamyl alcohol comprises the following steps: subjecting thioglycolic acid, cinnamyl alcohol, p-toluenesulfonic acid and toluene to a reflux reaction, and distilling under reduced pressure until no liquid is distilled out to obtain the modified cinnamyl alcohol; the reflux reaction is a reflux reaction at 110° C. for 4.0 hours; the dosage ratio of the thioglycolic acid, cinnamyl alcohol, p-toluenesulfonic acid and toluene is 20g:52g:3.2g:160mL.
[0032] Example 2
[0033] A method for preparing a composite flocculant for water treatment process comprises the following steps:
[0034] S1. Mix montmorillonite and hydrochloric acid solution, perform ultrasonic treatment, filter out, vacuum dry to constant weight, add anhydrous ethanol and coupling agent, grind and mix, filter, wash, dry to constant weight, calcine at high temperature, and cool to room temperature to obtain modified montmorillonite; wherein the mass ratio of montmorillonite, hydrochloric acid solution, anhydrous ethanol and coupling agent is 9:42:32:2.4; the coupling agent is aluminate coupling agent DL-411; the mass fraction of the hydrochloric acid solution is 15%; the ultrasonic treatment is 9 minutes at 450W power; the grinding and mixing time is 55 minutes; the washing is three times of washing with anhydrous ethanol; the calcination is calcined at 310°C for 1.8 hours; the vacuum drying temperature is 85°C; the drying temperature is 110°C;
[0035] S2. In a nitrogen atmosphere, the modified montmorillonite and chitosan solution are mixed and ground, and after adding citral solution and stirring at constant temperature, the solid is filtered, washed, and vacuum dried to constant weight to obtain a prefabricated flocculant; the mass ratio of the modified montmorillonite, chitosan solution and citral solution is 13:115:38; the chitosan solution is formed by mixing chitosan, acetic acid and deionized water in a mass ratio of 1.1:0.35:65; the citral solution is formed by mixing citral and anhydrous ethanol in a mass ratio of 2.6:32; the grinding time is 35 minutes; the constant temperature stirring is stirring at 55°C and 550rpm for 5.5 hours; the washing is washing three times with anhydrous ethanol; the vacuum drying temperature is 85°C;
[0036] S3. Mix the preformed flocculant, modified cinnamyl alcohol, anhydrous ethanol and initiator, heat and stir, filter out the solid, wash, and vacuum dry to constant weight to obtain; wherein the mass ratio of the preformed flocculant, modified cinnamyl alcohol, anhydrous ethanol and initiator is 22:3.4:75:0.11; the initiator is azobisisoheptanonitrile; the heating and stirring is stirring at 70°C and 450rpm for 5.5h; the washing is washing three times with anhydrous ethanol; the vacuum drying temperature is 85°C.
[0037] The preparation method of the modified cinnamyl alcohol comprises the following steps: subjecting thioglycolic acid, cinnamyl alcohol, p-toluenesulfonic acid and toluene to a reflux reaction, and distilling under reduced pressure until no liquid is distilled out to obtain the modified cinnamyl alcohol; the reflux reaction is a reflux reaction at 115° C. for 4.2 hours; the dosage ratio of the thioglycolic acid, cinnamyl alcohol, p-toluenesulfonic acid and toluene is 22 g:56 g:3.5 g:165 mL.
[0038] Example 3
[0039] A method for preparing a composite flocculant for water treatment process comprises the following steps:
[0040] S1. Mix montmorillonite and hydrochloric acid solution, perform ultrasonic treatment, filter out, vacuum dry to constant weight, add anhydrous ethanol and coupling agent, grind and mix, filter, wash, dry to constant weight, calcine at high temperature, and cool to room temperature to obtain modified montmorillonite; wherein the mass ratio of montmorillonite, hydrochloric acid solution, anhydrous ethanol and coupling agent is 10:45:35:2.5; the coupling agent is aluminate coupling agent DL-411; the mass fraction of the hydrochloric acid solution is 15%; the ultrasonic treatment is 10 minutes at 500W power; the grinding and mixing time is 60 minutes; the washing is three times of washing with anhydrous ethanol; the calcination is calcined at 320°C for 2.0 hours; the vacuum drying temperature is 90°C; the drying temperature is 110°C;
[0041] S2. In a nitrogen atmosphere, the modified montmorillonite and chitosan solution are mixed and ground, and after adding citral solution and stirring at constant temperature, the solid is filtered, washed, and vacuum dried to constant weight to obtain a prefabricated flocculant; the mass ratio of the modified montmorillonite, chitosan solution and citral solution is 14:120:40; the chitosan solution is formed by mixing chitosan, acetic acid and deionized water in a mass ratio of 1.2:0.4:70; the citral solution is formed by mixing citral and anhydrous ethanol in a mass ratio of 2.8:35; the grinding time is 40 minutes; the constant temperature stirring is stirring at 60°C and 600 rpm for 6 hours; the washing is washing three times with anhydrous ethanol; the vacuum drying temperature is 90°C;
[0042] S3. Mix the preformed flocculant, modified cinnamyl alcohol, anhydrous ethanol and initiator, heat and stir, filter out the solid, wash, and vacuum dry to constant weight to obtain; wherein the mass ratio of the preformed flocculant, modified cinnamyl alcohol, anhydrous ethanol and initiator is 23:3.6:80:0.12; the initiator is azobisisoheptanonitrile; the heating and stirring is stirring at a temperature of 72°C and a speed of 500 rpm for 6 hours; the washing is washing three times with anhydrous ethanol; the vacuum drying temperature is 90°C.
[0043] The preparation method of the modified cinnamyl alcohol comprises the following steps: subjecting thioglycolic acid, cinnamyl alcohol, p-toluenesulfonic acid and toluene to a reflux reaction, and distilling under reduced pressure until no liquid is distilled out to obtain the modified cinnamyl alcohol; the reflux reaction is a reflux reaction at 120° C. for 4.5 hours; the dosage ratio of the thioglycolic acid, cinnamyl alcohol, p-toluenesulfonic acid and toluene is 23g:60g:3.8g:170mL.
[0044] Comparative Example 1
[0045] Compared with Example 3, the difference in Comparative Example 1 is that no coupling agent is used in step S1, and the other components, preparation steps and parameters are the same.
[0046] Comparative Example 2
[0047] Compared with Example 3, the difference in Comparative Example 2 is that chitosan is not used in step S2, and the other components, preparation steps and parameters are the same.
[0048] Comparative Example 3
[0049] Compared with Example 3, the difference in Comparative Example 3 is that citral is not used in step S2, and the remaining components, preparation steps and parameters are the same.
[0050] Comparative Example 4
[0051] Compared with Example 3, the difference in Comparative Example 4 is that step S3 uses cinnamyl alcohol instead of modified cinnamyl alcohol, and the other components, preparation steps and parameters are the same.
[0052] Comparative Example 5
[0053] Compared with Example 3, the difference in Comparative Example 5 is that step S3 is not performed, and the remaining components, preparation steps and parameters are the same.
[0054] Comparative Example 6
[0055] Compared with Example 3, Comparative Example 6 is different in that deionized water is used instead of hydrochloric acid solution in step S1, and the other components, preparation steps and parameters are the same.
[0056] The flocculants prepared in Examples 1-3 and Comparative Examples 1-6 were tested for COD removal, respectively. The COD content of the sewage was 195 mg / L. The COD removal rates were calculated. The calculation results are shown in Table 1.
[0057] Table 1
[0058]
[0059]
[0060] From the test results in Table 1, it can be seen that compared with Comparative Examples 1-6, the flocculants prepared in Examples 1-3 of the present invention have significant removal effects on COD in sewage treatment; through comparative analysis, it can be seen that this is because the present invention treats montmorillonite with hydrochloric acid to remove its own impurities, increase its interlayer distance, and introduce more active sites, and then in-situ calcinates an aluminate coupling agent on the surface of montmorillonite to generate porous alumina, which can increase the stability of montmorillonite while increasing its specific surface area, and promote chitosan to enter and form a network structure through hydrogen bonds and coordination bonds, further increasing its active sites, and then introduces hydrophobic citral, and forms a graft with modified cinnamyl alcohol through multiple unsaturated double bonds on citral, introduces a hydrophobic rigid benzene ring structure, and increases stability while increasing the adsorption capacity of pollutants by utilizing the hydrophobic effect, and the thiophenol group on the modified cinnamyl alcohol can further improve the COD removal rate of the flocculant. In summary, the present invention prepares an organic / inorganic composite flocculant, increases its stability, and utilizes a variety of mechanisms such as hydrophobic effect, electrostatic effect, and coordination effect on metal elements to significantly improve the flocculant's adsorption capacity for pollutants.
[0061] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technical personnel in this field can make some changes or modify the technical contents disclosed above into equivalent embodiments without departing from the scope of the technical solution of the present invention. However, any indirect modification, equivalent change and modification made to the above embodiments according to the technical essence of the present invention without departing from the content of the technical solution of the present invention still fall within the scope of the technical solution of the present invention.
Claims
1. A method for preparing a composite flocculant for water treatment process, characterized in that: The preparation method comprises the following steps: S1. Mixing montmorillonite and hydrochloric acid solution, ultrasonically treating the mixture, filtering out the mixture, vacuum drying the mixture to constant weight, adding anhydrous ethanol and a coupling agent, grinding and mixing the mixture, filtering, washing the mixture, drying the mixture to constant weight, calcining the mixture at high temperature, and cooling the mixture to room temperature to obtain modified montmorillonite; S2. Under a nitrogen atmosphere, the modified montmorillonite and chitosan solution are mixed and ground, and the citral solution is added and stirred at a constant temperature, and then the solid is filtered out, washed, and vacuum dried to a constant weight to obtain a prefabricated flocculant; S3. The prefabricated flocculant, modified cinnamyl alcohol, anhydrous ethanol and initiator are mixed and heated with stirring, solids are filtered out, washed and vacuum dried to constant weight to obtain the product.
2. The method for preparing a composite flocculant for water treatment process according to claim 1, characterized in that: In step S1, the mass ratio of the montmorillonite, the hydrochloric acid solution, the anhydrous ethanol and the coupling agent is 8-10:40-45:30-35:2.2-2.5; and the coupling agent is an aluminate coupling agent.
3. The method for preparing a composite flocculant for water treatment process according to claim 1, characterized in that: In step S1, the mass fraction of the hydrochloric acid solution is 15%; the ultrasonic treatment is performed at a power of 400-500 W for 8-10 min; the grinding and mixing time is 50-60 min; the washing is performed three times with anhydrous ethanol; and the calcination is performed at a temperature of 300-320° C. for 1.5-2.0 h.
4. The method for preparing a composite flocculant for water treatment process according to claim 1, characterized in that: In step S2, the mass ratio of the modified montmorillonite, chitosan solution and citral solution is 12-14:110-120:35-40; the chitosan solution is formed by mixing chitosan, acetic acid and deionized water in a mass ratio of 1.0-1.2:0.3-0.4:60-70; and the citral solution is formed by mixing citral and anhydrous ethanol in a mass ratio of 2.5-2.8:30-35.
5. The method for preparing a composite flocculant for water treatment process according to claim 1, characterized in that: In step S2, the grinding time is 30-40 minutes; the constant temperature stirring is stirring at 50-60°C and 500-600 rpm for 5-6 hours; and the washing is washing three times with anhydrous ethanol.
6. The method for preparing a composite flocculant for water treatment process according to claim 1, characterized in that: In step S3, the mass ratio of the prefabricated flocculant, modified cinnamyl alcohol, anhydrous ethanol and initiator is 20-23:3.2-3.6:70-80:0.10-0.12; the initiator is azobisisoheptonitrile.
7. The method for preparing a composite flocculant for water treatment process according to claim 1, characterized in that: In step S3, the heating and stirring is stirring at a temperature of 68-72° C. and a rotation speed of 400-500 rpm for 5-6 hours; and the washing is washing three times with anhydrous ethanol.
8. The method for preparing a composite flocculant for water treatment process according to claim 1, characterized in that: The preparation method of the modified cinnamyl alcohol comprises the following steps: subjecting thioglycolic acid, cinnamyl alcohol, p-toluenesulfonic acid and toluene to a reflux reaction, and performing reduced pressure distillation until no liquid is distilled out to obtain the modified cinnamyl alcohol.
9. The method for preparing a composite flocculant for water treatment process according to claim 8, characterized in that: The reflux reaction is carried out at 110-120° C. for 4.0-4.5 hours; the dosage ratio of the thioglycolic acid, cinnamyl alcohol, p-toluenesulfonic acid and toluene is 20-23 g: 52-60 g: 3.2-3.8 g: 160-170 mL.
10. A composite flocculant for water treatment prepared by the preparation method according to any one of claims 1 to 9.
Citation Information
Cited By
Modified high-performance fiber material and preparation method thereof
CN120984247A